Early therapy assessment of combined anti‐DR5 antibody and carboplatin in triple‐negative breast cancer xenografts in mice using diffusion‐weighted imaging and 1H MR spectroscopy. Issue 6 (22nd October 2013) - Zhai, Guihua; Kim, Hyunki; Sarver, David; Samuel, Sharon; Whitworth, Lee; Umphrey, Heidi; Oelschlager, Denise K.; Beasley, T. Mark; Zinn, Kurt R.
Abstract : Purpose: To assess the early response of triple‐negative breast‐cancer (TNBC) following TRA‐8 and carboplatin therapy using DWI and MRS in 2LMP and SUM159 mouse models. Materials and Methods: Four groups (n = 5/group) of each model were untreated or treated with carboplatin, TRA‐8, and combination, respectively. DWI and MRS were applied on 0, 3, and 7 days after therapy initiation, and all tumors were collected thereafter for terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) staining. The changes in intratumoral apparent diffusion coefficient (ADC) and fat–water ratios (FWRs) were compared with tumor volume changes and apoptotic cell densities. Results: Mean ADC values of 2LMP and SUM159 tumors significantly increased 4 ± 4% and 37 ± 11% during 7 days of combination therapy, respectively, as compared to control groups ( P  < 0.05). Similarly, mean FWRs of 2LMP and SUM159 tumors significantly increased 102 ± 30% and 126 ± 52%, respectively, for 7 days of combined treatment ( P  < 0.05). The changes of the mean ADC values for 3 days (or FWRs for 7 days) were linearly proportional to either the mean volume changes or apoptotic cell densities in both models. Conclusion: DWI and MRS assessed the early tumor response to TRA‐8 and carboplatin in TNBC mouse models.J. Magn. Reson. Imaging 2014;39:1588–1594 . ©2013 Wiley Periodicals, Inc .